Students’ Perceptions of Interactive Multimedia in Learning Vocabulary - Darmiati, Darmiati (Majesty Journal, 2022)
Interactive multimedia is a learning delivery system that uses recorded sights, audio, and video information that is delivered under computer control for a review that not only sees and hears pictures and sounds, but also responds to them. This research is focused to find out what students’ perceptions on the use of interactive multimedia in learning vocabulary at Madrasah Ibtidaiyah Negeri 2 Enrekang. This research employed descriptive method using qualitative approach. The population were the fifth class in Madrasah Ibtidaiyah Negeri 2 Enrekang in 2020/2021 academic years. Total sampling was used in this research with total 29 students. The instrument used in this research were questionnaire. The Result of this research showed that students had a positive perception in learning vocabulary using interactive multimedia. This is evidenced by the frequency of students’ answer is laid in 64,51% (19 of 29 students) for positive category.